A multisite focus group study of US adult women's beliefs and assumptions about bladder health and function. Issue 7 (12th July 2022) - Williams, Beverly Rosa; Burgio, Kathryn L.; Hebert‐Beirne, Jeni; James, Aimee; Kenton, Kimberly; LaCoursiere, Daphne Yvette; Rickey, Leslie; Brady, Sonya S.; Kane Low, Lisa; Newman, Diane K.; ,
Abstract: Aims: This analysis explored and characterized the ideas adult women have about how the bladder works, the assumptions guiding their bladder‐related behaviors, and the beliefs they hold about how their behaviors affect bladder health. Methods: This was a directed content analysis of qualitative data from the Study of Habits, Attitudes, Realities, and Experiences, a focus group study conducted at seven United States research centers (July 2017 to April 2018). Participants were 316 adult women organized by four age categories (age range: 18−93 years). Analysis and interpretation focused on the "bladder assumptions and beliefs" code using a transdisciplinary lens and inductive approach. Results: During their focus group discourse, participants exhibited a speculative mode of thinking about bladder health and function characterized by uncertainty about how the bladder works. They described the bladder as a mechanism for cleansing the body of impurities, viewing it as part of a larger interconnected bodily system to enable the body to stay healthy. They saw it as susceptible to anatomical changes, such as those related to pregnancy and aging. The women also postulated perceived relationships between bladder function and several health behaviors, including eating healthy foods, staying hydrated, engaging in physical activity and exercise, and adopting specific toileting and hygiene practices. Conclusions: The findings underscore the importance of guidance from healthcare professionals and systematic community based educational programs for promoting women's understanding about bladder health and empowering them to exert agency to engage in healthy bladder behaviors.